From Ebers to EVARs - Bobadilla, Joseph L. (AORTA, 2013)
Pathology of the aorta has been recognized for nearly three and a half millennia, dating back to the first recorded description in the scrolls of Ebers, circa 1550 BC. Since that time, treatment has evolved from magical medicinal remedies and incantations to nearly outpatient percutaneous interventions. From the first attempts at open surgical reconstruction in the 1700s and 1800s, to the latest generations of endovascular devices, innovative pioneers have pushed the envelope of surgical technique in developing unique and novel strategies to treat the ever complex pathology of the aorta. We are just now beginning to understand these pathologies at the molecular and genetic levels, and with that expansive extent of investigation enters a journal, dedicated solely to the aorta. With this article, we hope to illuminate the rich and deep history of aortic pathology, and the innovations leading to the technology of today. A firm understanding of our past provides a strong foundation for further growth into the future.